2022
DOI: 10.3389/fpsyg.2022.860687
|View full text |Cite
|
Sign up to set email alerts
|

The Test Based on Meta-Analysis on “Does Workaholism Prefer Task Performance or Contextual Performance?”

Abstract: The relationship between workaholism and work performance is explored by meta-analysis in this article. After searching relevant references, we had gained 94 individual effect sizes (n = 57,352), 45 individual samples, and 37 references. Through the heterogeneity test, it was shown that the random effect model is more suitable. The main effect analysis showed that there is a significant positive correlation between workaholism, working excessively, working compulsively, and work performance, and further analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Although it is not listed in their job description that they need to update their skills and knowledge to the changing current demands, they still do so to contribute to the organization. This is aligned with the study by Cheng and Gu (2022) that contextual performance is the behaviors and efforts made by employees that are not directly related to their work.…”
Section: The Level Of Job Performance Among Lower-level Employees In ...supporting
confidence: 82%
See 1 more Smart Citation
“…Although it is not listed in their job description that they need to update their skills and knowledge to the changing current demands, they still do so to contribute to the organization. This is aligned with the study by Cheng and Gu (2022) that contextual performance is the behaviors and efforts made by employees that are not directly related to their work.…”
Section: The Level Of Job Performance Among Lower-level Employees In ...supporting
confidence: 82%
“…Next, contextual performance is defined as behaviour that contributes to organizational goals by supporting its social and psychological environment such as performing tasks beyond job duties and being proactive and cooperative (Kalia & Bhardwaj, 2019). Cheng and Gu (2022) stated that contextual performance is the behaviors and efforts made by employees that are not directly related to their work. It also may provide a positive outlook towards colleagues and naturally encourage them to do tasks that are not within their job scope.…”
Section: Figurementioning
confidence: 99%
“…The present study's estimated prevalence suggests that roughly 1 in 7 might be affected with workaholism. This indicates that workaholism is a prevalent issue which is a concern as it is well known that workaholism takes a heavy toll on people's health and wellbeing (Robinson et al, 2006;Schaufeli et al, 2008a;Andreassen et al, 2013aAndreassen et al, , 2016Andreassen et al, , 2018aHaar and Roche, 2013;Matsudaira et al, 2013;Shimazu et al, 2015;Clark et al, 2016;Salanova et al, 2016;Yang et al, 2020;Balducci et al, 2021;Galdino et al, 2021;Chang et al, 2022;Cheng and Gu, 2022;Sarfaraz et al, 2022).…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Some have assessed the link between workaholism and personality (e.g., Patel et al, 2012;Clark et al, 2016;Kun et al, 2020b). Others have chosen to direct attention toward workaholism and specific work-related constructs such as work performance (Cheng and Gu, 2022) and work engagement (Lee et al, 2022). To our knowledge there has not yet been conducted a meta-analysis on the prevalence of workaholism.…”
Section: Present Meta-analytic Research On Workaholismmentioning
confidence: 99%
“…Working excessively, in turn, can negatively influence workers' personal sphere, leading to higher WFC. The literature has widely demonstrated that individuals with workaholic tendencies are at a higher risk of experiencing WFC [33], and this relationship is even stronger in the case of the behavioral component [20,28]. For example, individuals who tend to work excessively spend more time on work activities, paying less attention to the family environment [34].…”
Section: The Mediating Role Of Working Excessively In the Association...mentioning
confidence: 99%